Recursos didácticos del área de matemática y su contribución en el proceso de enseñanza/aprendizaje a estudiantes de la escuela educación básica “Manuel Villamarín Ortiz”, cantón Babahoyo, provincia los ríos - Arias Delgado, Verónica Mariella (2015)
The purpose of this research is aimed at finding teaching resources for the area most suitable mathematics and according to the level of students in the fifth and sixth basic year of education Unit Manuel Villamarín Ortiz it is important to the management of teaching resources appropriate to optimizing the teaching process. To achieve these objectives, it is necessary to make an exploration of the different teaching resources currently employed and who are available to teachers. The proposal will implement an appropriate teaching resource for the teaching and learning of mathematics; thus enabling more find a way to raise student learning. The theoretical foundation is developed with issues related to the variables presented in the problem; use of educational resources and teaching-learning process, taking into account its dimensions and indicators. This research has a qualitative and quantitative approach and is based on the form of a socio-educational project. The level of research is descriptive exploratory. The project calls for two types of research: Field and acknowledged. The sample for this research are